Aromatase-induced endogenous estrogen promotes tumour metastasis through estrogen receptor-α/matrix metalloproteinase 12 axis activation in castration-resistant prostate cancer. (28th December 2019) - Liang, Zhixian; Cao, Jiasong; Tian, Lei; Shen, Yongmei; Yang, Xu; Lin, Qimei; Zhang, Ran; Liu, Haitao; Du, Xiaoling; Shi, Jiandang; Zhang, Ju
Abstract: Castration-resistant prostate cancer (CRPC) following androgen deprivation therapy remains a major obstacle advanced prostate cancer management. Aromatase catalyzes estrogen from androgens, yet the role of aromatase-generated endogenous estrogen in CRPC is poorly understood. In this study, we assessed the expression and function of aromatase in CRPC. We found that aromatase expression was significantly increased in CRPC tissues and cell lines. In some prostate cancer cell lines, aromatase was predominantly expressed in CD44 + subsets. Bicalutamide treatment significantly increased aromatase expression, and CYP19A1 expression positively correlated with estrogen responses and epithelial-mesenchymal transition. Aromatase knockdown in PC3 cells reduced invasiveness and decreased metastasis-related gene expression. The aromatase inhibitor, letrozole, attenuated tumour metastasis in castrated PC3-xenograft mice. Mechanistically, aromatase-induced endogenous estrogen promoted estrogen receptor-α (ERα) binding to matrix metalloproteinase 12 (MMP12) promoter estrogen response element (ERE). MMP12 co-localized with CD44 on the cell membrane and MMP12 knockdown significantly reduced estradiol-induced PC3 invasion. Taken together, our findings indicated that increased endogenous estrogen, catalysed by elevated aromatase levels, enhanced MMP12 expression via ERα, participated in CRPC progression and promoted tumour metastasis. Thus, aromatase represents a potential novel therapeutic target for CRPC. Highlights: Aromatase expression was markedly increased in CRPC. Aromatase was expressed predominantly in CD44 + prostate cancer stem-like cells. Estrogen catalysed by aromatase enhanced ERα-dependent MMP12 expression. Targeting aromatase attenuated the metastasis of CRPC. Aromatase represents an attractive target for therapies in CRPC treatment.